Предмет: Математика, автор: sanyastel270

Обчистити:
(-1 3/7*4 2/3+1 7/9)*(-3/4)

Ответы

Автор ответа: kingwolfrap
0

(-1 3/7*4 2/3+1 7/9)*(-3/4)=(-10/7* 14/3 + 16/9)*(-3/4)=(-20/3+16/9)*(-3/4)=(-60/9+16/9)*(-3/4)=-44/9*(-3/4)=11/3=3 2/3

Автор ответа: oksik1970
0

Ответ:

10 \frac{1}{3}

Решение:

( - 1 \frac{3}{7}   \times 4 \frac{2}{3}  + 1 \frac{7}{9} ) \times ( -  \frac{3}{4} ) = ( -  \frac{10 \times 14}{3 \times 3}  +  \frac{16}{9} ) \times ( -  \frac{3}{4} ) =  \frac{10 \times 14 \times 3}{3 \times 3 \times 4}  -  \frac{16 \times 3}{9 \times 4}  =  \frac{5 \times 7}{3}  -  \frac{4}{3}  =  \frac{35 - 4}{3}  =  \frac{31}{3}  = 10 \frac{1}{3}

Похожие вопросы